MEDIA FIELD AND INTERNET OPPORTUNITIES ("Conference on Universal Science Research 2023", 2023)
In this article, information about the history and understanding of all the possibilities of the Internet is given, and the majority of people in the world are using the Internet, which means that people and society do not stand still, they are always changing, and the time we live in is called the era of globalization. information is given that it has become a common situation.